A DFT investigation on the potential of beryllium oxide (Be12O12) as a nanocarrier for nucleobases. - Mahmoud A A Ibrahim; Maggie N S Hanna; Al-Shimaa S M Rady; Peter A Sidhom; Shaban R M Sayed; Mohamed A El-Tayeb; Ahmed M Awad; Hatem Tallima; Tamer Shoeib (PLoS ONE)
The study of the interactions between biomolecules and nanostructures is quite fascinating. Herein, the adsorption propensity of beryllium oxide (Be12O12) nanocarrier toward nucleobases (NBs) was investigated. In terms of DFT calculations, the adsorption tendency of Be12O12 toward NBs, including cytosine (NB-C), guanine (NB-G), adenine (NB-A), thymine (NB-T), and uracil (NB-U), was unveiled through various configurations. Geometrical, electronic, and energetic features for Be12O12, NBs, and their associated complexes were thoroughly evaluated at M06-2X/6-311+G** level of theory. The potent adsorption process within NBs∙∙∙Be12O12 complexes was noticed through favorable interaction (Eint) and adsorption (Eads) energies with values up to -53.04 and -38.30 kcal/mol, respectively. Generally, a significant adsorption process was observed for all studied complexes, and the favorability followed the order: NB-C∙∙∙ > NB-G∙∙∙ > NB-A∙∙∙ > NB-T∙∙∙ > NB-U∙∙∙Be12O12 complexes. Out of all studied complexes, the most potent adsorption was found for NB-C∙∙∙Be12O12 complex within configuration A (Eint = -53.04 kcal/mol). In terms of energy decomposition, SAPT analysis revealed electrostatic (Eelst) forces to be dominant within the studied adsorption process with values up to -99.88 kcal/mol. Analyzing QTAIM and NCI, attractive intermolecular interactions within the studied complexes were affirmed. From negative values of thermodynamic parameters, the nature of the considered adsorption process was revealed to be spontaneous and exothermic. Regarding density of state, IR, and Raman analyses, the occurrence of the adsorption process within NBs∙∙∙Be12O12 complexes was confirmed. Noticeable short recovery time values were observed for all studied complexes, confirming the occurrence of the desorption process. The findings provided fundamental insights into the potential application of Be12O12 nanocarrier in drug and gene delivery processes.